Controllable synthesis and morphology-dependent photoluminescence properties of well-defined one-dimensional Zn2GeO4:Mn2+ nanostructures. (March 2018) - Li, Yanshen; Zhao, Ankang; Chen, Chunyan; Zhang, Cuimiao; Zhang, Jinyu; Jia, Guang
Abstract: A variety of uniform and well-dispersed one-dimensional Zn2 GeO4 :Mn 2+ phosphors have been synthesized via a facile solvothermal process with H2 O/EG as solvent. During the synthesis process, the component of solvent and the addition of PEG surfactant play an important role in determining the structure, particle size, and morphology of the final product. Under ultraviolet light excitation, the pure Zn2 GeO4 sample shows bluish-white emission which is attributed to the native defects present in the Zn2 GeO4 host. When Zn 2+ ions are partially substituted by Mn 2+, the as-synthesized Zn2 GeO4 :Mn 2+ samples exhibit intense green emission that corresponds to the d-d transition ( 4 T1 → 6 A1 ) of Mn 2+ ions. The luminescence mechanisms of the Zn2 GeO4 :Mn 2+ samples were investigated in detail by using the CASTEP code based on density functional theory (DFT). It is expected that the as-synthesized Zn2 GeO4 :Mn 2+ phosphors can be potentially applied in lighting, optical displays, and optoelectronic devices. Graphical abstract: Highlights: A variety of 1D Zn2 GeO4 :Mn 2+ phosphors were synthesized via a solvothermal process. The solvent and surfactant have effect on structure and morphology of the products. The pure and Mn 2+ -doped Zn2 GeO4 samples exhibit bluish-white and green emissions. The dependence of luminescence properties on different morphologies was investigated. The PL mechanisms were discussed by CASTEP code based on density functional theory.